(untitled) (Medical Forum Monthly, 2024)
Objective: To study the current trends of Epidemiological Profile of Pesticide Poisoning Cases reporting at a tertiary care hospital of Sindh. Study Design: Prospective observational study Place and Duration of Study: This study was conducted at the Chandka Medical College Hospital from January 2015 to May 2016. Materials and Methods: A sample of 60 agriculture pesticide poisoning cases was studied in accordance to the inclusion and exclusion criteria. Biodata and physical examination were noted in the proforma. The patient data was kept confidential. Written informed consent was mandatory. SPSS 22.0 (IBM, Incorporation, USA) was available for the data analysis at 95% Confidence interval (P≤0.05). Results: Mean± SD age noted was 43.5 ± 9.6 years; majority belonged to the 4th decade of life (p=0.0001). Of 60 subjects, 51 (85%) were male and 9 (15%) were female (p=0.0001). Male to female ratio was 5.6:1. Pinpoint pupil, hypotension, unconsciousness, sweating, cyanosis, and bradypnea were noted in the majority of study subjects. Medicolegal aspects of poisoning show 51.6% were accidental, 31.6 were suicidal and 16.6% were homicidal cases. Conclusion: The findings of present study show accidental agricultural pesticide poisoning as most common followed by suicidal and homicidal poisoning. Legal restrictions of safe use of pesticides should be implemented urgently and strictly.